Pengaruh Prestasi, Lupa, dan Kejenuhan dalam Proses Belajar Mengaji Pada Pendidikan Islam Anak Usia Dini - Rifaldi, Rifki; Aep Tata Surya (Universitas Negeri Surabaya, 2025)
This study aims to examine the influence of achievement, tendency to forget, and boredom in the process of learning to recite the Quran in early childhood in Islamic educational institutions. The approach used is qualitative with a field study method, where data is obtained through observation, interviews, and documentation of learning activities in one of the Islamic PAUDs. The results of the study indicate that achievement plays an important role in increasing children's motivation and enthusiasm for learning, while forgetting and boredom are the main obstacles that affect the consistency and effectiveness of learning. Children who are given appreciation regularly tend to show better development, while boredom often arises due to monotonous learning methods. To overcome this, creative, varied, and fun learning strategies are needed, as well as the active involvement of parents and teachers in creating a conducive learning atmosphere. Thus, the process of learning to recite the Quran in early childhood will be more effective if supported by a holistic approach that is responsive to the needs of children's development.